ODONTOGENIC CYSTS IN TERTIARY CARE RIMS TEACHING HOSPITAL-RETROSPECTIVE STUDY - Dr. Tirumalrao; Dr. Jyothi L; Dr. Amarvarma; Dr. Amarvarma; Dr. Bapugouda Mulimani; Dr. Shweta Danaraddi; Dr. Geeta marishetter (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
INTRODUCTION Cyst of the odontogenic origin is a destructing lesion which varies in its size. It can be inflammatory or epithelial, based upon its origin. These lesions are of importance because of their direct concern with patients’ facial aesthetics and masticatory function. The aim of the study is to assess the frequency of odontogenic cyst in maxillary & mandibular region. METHODS The retrospective study was done among 500 odontogenic cysts cases during the period from January 2018 to September 2023 from RIMS Hospital of Raichur. Tissue samples with cystic lesions involving the jaws were collected. Patient’s demographic data was recorded. Data collected was statistically analysed using descriptive analyses using SPSS version 25.0. RESULTS Maximum cases were in the age group of 18-35 years (60%). Number of male subjects was 75% and number of female subjects was 25% cases. Frequency of cyst in maxillary anterior region was 18%, in mandibular posterior region was 19%, in mandibular anterior region was 40% and mandibular posterior region was 23%. The most common type of cyst found were radicular (45), dentigerous (23) and odontogeic keratocyst (14). CONCLUSION The most common type of cyst present was radicular cyst. This study provides data on the prevalence of odontogenic cystic lesions in the jaws, specifically in relation to age, gender, and location preference.